The Fasting of Ramadan: Forming Positive Personal Character - Makmun, Sukron (Bina Nusantara University, 2016)
Article discussed the relationship between the fasting of Ramadan with the formation of a positive character. The purposes of this article were exploring the meaning and finding the influence of fasting in shaping the character of a person. A descriptive-analytical method was applied in the research. The procedures were data collection, data classification, data analysis, and conclusions. The source of the data was gained from information available in the literature study. The data was analyzed by using content analysis method (content analysis), which was an attempt to explore the symbolic meaning of the message or the contents. The result shows that Ramadan fasting worship performed by Muslims for 29 or 30 days is not just limited to the ritual, but it also contributes to the formation of one's character when is viewed from the perspective of the character education. It can be concluded that fasting is done in earnest to bring a positive influence on the formation of character for someone. The positive character built through fasting are the habit of appreciating the time, keeping the rights of others, being honest and patient, and the habit of giving and being helpful.